Level of accuracy of diagnoses recorded in discharge summaries: A cohort study in three respiratory wards. Issue 1 (14th August 2018) - Tsopra, Rosy; Wyatt, Jeremy C.; Beirne, Paul; Rodger, Kirsty; Callister, Matthew; Ghosh, Dipansu; Clifton, Ian J.; Whitaker, Paul; Peckham, Daniel
Abstract: Rationale: One of the key functions of the discharge summary is to convey accurate diagnostic description of patients. Inaccurate or missing diagnoses may result in a false clinical picture, inappropriate management, poor quality of care, and a higher risk of re‐admission. While several studies have investigated the presence or absence of diagnoses within discharge summaries, there are very few published studies assessing the accuracy of these diagnoses. The aim of this study was to measure the accuracy of diagnoses recorded in sample summaries, and to determine if it was correlated with the type of diagnoses (eg, "respiratory" diagnoses), the number of diagnoses, or the length of patient stay. Methods: A prospective cohort study was conducted in three respiratory wards in a large UK NHS Teaching Hospital. We determined the reference list of diagnoses (the closest to the true state of the patient based on consultant knowledge, patient records, and laboratory investigations) for comparison with the diagnoses recorded in a discharge summary. To enable objective comparison, all patient diagnoses were encoded using a standardized terminology (ICD‐10). Inaccuracy of the primary diagnosis alone and all diagnoses in discharge summaries was measured and then correlated with type of diseases, number of diagnoses, and length of patient stay. Results: A total of 107 of 110 consecutive discharge summaries were analysed. The mean inaccuracy rate per discharge summary was 55% [95% CI 52 to 58%]. Primary diagnoses were wrong, inaccurate, missing, or mis‐recorded as a secondary diagnosis in half the summaries. The inaccuracy rate was correlated with the type of disease but not with number of diagnoses nor length of patient stay. Conclusion: Our study showed that diagnoses were not accurately recorded in discharge summaries, highlighting the need to measure and improve discharge summary quality.